Digitalization and the Information Society in Algeria: Digital Transformation Actors and Key Variables - Bouberka, Maria; Fadel, Sabah; Derrar, Hassan (Cyfryzacja i społeczeństwo informacyjne w Algierii: determinanty i uczestnicy transformacji cyfrowej, 2023)
The information society is a product of the intersection of socio-historical-technological contexts, where the development of science and industry has a global reach. The pervasiveness of new information and communication technologies makes it an essential component of a new civilization, affecting every country in varying degrees. Although this techniques approach is grounded in some truth, it neglects other vital aspects that challenge the idea of an information society that prioritizes human needs. The leading nations have achieved this through active research and development, driven by government involvement and the significant contributions of universities. Furthermore, the collaboration of diverse economic, institutional, social, and civic actors has played an essential role in its advancement. However, constructing and promoting an information society transcends infrastructure. It involves political actions that consider the socio-technological nature of this development and its impact on society and other sectors of activity. The objective of this article is twofold. On the one hand, the study analysed the situation of Algeria and its position in relation to other countries regarding the information society, and the other examined the factors that influence the development of the information society in Algeria, trying to identify the most important ones. Finally, the authors proposed a development strategy in this area. The research thesis was formulated as follows: What are the key variables that have an impact on the development of digitalization and the information society in Algeria? Thus, the regulatory frameworks of the most advanced countries are central to the initiatives aimed at its development. To foster the emergence of an information society in Algeria, solidarity must be strengthened, diversity promoted, and the potential of all citizens catalysed.
Econometrics = Ekonometria, 2023, Vol. 27, No. 2, s. 21-44
Keywords: information society; digitalization; Network Readiness Index; information and communication technologies; społeczeństwo informacyjne; cyfryzacja; wskaźnik gotowości sieci; ICT; Algieria